Additional Resource Allocation for improving Fairness in WiMAX - Khalid Mahmood Awan; Abdul Hanan Abdullah; Khalid Hussain (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
IEEE 802.16 standard provides resources to both service classes Constant Bit Rate (CBR) and Variable Bit Rate (VBR). Both of these services required enough resources to transmit data efficiently.Considering available literature there is a gap to provide additional resources for fulfillment of the required service class.In this paper we propose a Service Based Fair Resource Allocation (SBFRA) Mechansim, for evaluating the required service from Subscriber (SS) along with the channel condition. Our proposed model evaluates, for providing the required service to SS how much additional resource will be required. In this model we introduced Priority Queue Scheduling Methodology for providing additional resources as per channel condition. In this paper we made comparison with and without proposed model on both traffic, CBR and VBR. We experiment that our proposed model manages the user request by providing them additional resources as required for satisfaction. Their request handled in Priority Queue Scheduling based mechanism. Results shows, that we achieve improvement by providing the additional resource on fair scheduling basis. To achieve the required performance for fairness we have to compromise on with delay.